Actin Depolymerization Drives Actomyosin Ring Contraction during Budding Yeast Cytokinesis - Pinto, Inês Mendes (2012)
Actin filaments and myosin-II are evolutionarily conserved force generating components of the contractile ring during cytokinesis. Here we show that in budding yeast actin filament depolymerization plays a major role in actomyosin ring constriction. Cofilin mutation or chemically stabilizing actin filaments attenuates actomyosin ring constriction. Deletion of myosin-II motor domain or the myosin regulatory light chain reduced the contraction rate and also the rate of actin depolymerization in the ring. We constructed a quantitative microscopic model of actomyosin ring constriction via filament sliding driven by both actin depolymerization and myosin-II motor activity. Model simulations based on experimental measurements supports the notion that actin depolymerization is the predominant mechanism for ring constriction. The model predicts invariability of total contraction time irrespective of the initial ring size as originally reported for C elegans embryonic cells. This prediction was validated in yeast cells of different sizes due to having different ploidies.